ANALYZING STUDENTS’ ERRORS IN WRITING COMPOSITION. A THESIS. TEACHERS TRAINING AND EDUCATION FACULTY. CATHOLIC UNIVERSITY OF SAINT THOMAS. - Simbolon, Verawati R.; Lumbanraja, Viator; Prima, Anna Stasya (Kairos English Language Teaching Journal, 2021)
The purpose of this research was to find out the errors made by the eleventh grade students of SMA Swasta Santu Petrus Sidikalang in writing composition in the academic year of 2020/2021. Errors were analyzed based on linguistic category taxonomy. Linguistic category taxonomy consists of morphology and syntax. The population of this research is 262 students and 56 is randomly taken as a sample. Based on the result of the data analysis, there are 169 errors made by the students on their writing compositions. Morphological errors is 85 (50,29%) and syntactical errors is 84 (49,69%). Morphological errors that students made in morphology of linguistic category are definite aricle incorrect 14 (8,29%), possessive case incorrect 17 (10,05%), third person singular verb incorrect 25 (14,79%), simple past tense incorrect 28 (16,57%) and comparative adjective/adverb incorrect 1 (0,59%). In syntax there are noun phrase 40 (23,67%), verb phrase 28 (16,57%), verb-and-verb construction 5 (2,95%), word order 9 (5,32) and some trafnsformation 2 (1,18%). In conlusion the dominant errors made by the students is in morphology error.